2014
DOI: 10.1186/1472-6882-14-101
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Poria cocos reduces the production of inflammatory mediators by suppressing the NF-kappaB signaling pathway in lipopolysaccharide-stimulated RAW 264.7 macrophages

Abstract: BackgroundPoria cocos Wolf, a medicinal fungus, is widely used in traditional medicines in East Asian countries owing to its various therapeutic potentials. Although several studies have demonstrated the anti-inflammatory activity of this fungus, its underlying mechanisms have not yet been clearly defined.MethodsIn the present study, we have demonstrated the anti-inflammatory effects of ethanol extract of P. cocos (EEPC) in lipopolysaccaride (LPS)-stimulated RAW 264.7 macrophages. As inflammatory parameters, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…4 ), which is consistent with results of our previous studies in RAW 264.7 macrophages. 27 30 SF also has ability to inhibit the LPS-induced nuclear translocation of NF- κ B p65 and the degradation of I κ B-α. These effects might arise through suppression of the phosphorylation and proteasome-mediated degradation of its inhibitor I κ B-α, resulting in lower levels of NF- κ B transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…4 ), which is consistent with results of our previous studies in RAW 264.7 macrophages. 27 30 SF also has ability to inhibit the LPS-induced nuclear translocation of NF- κ B p65 and the degradation of I κ B-α. These effects might arise through suppression of the phosphorylation and proteasome-mediated degradation of its inhibitor I κ B-α, resulting in lower levels of NF- κ B transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in this study, we found that the integrity of intestinal villi and the expression of ZO-1 and E-cadherin in the rats of BPHW decoction were ameliorated, while the intestinal expression of TLR-4 and NF-κB of rats, as well as the contents of TNF-α, IL-1β, and IL-6 was also significantly lower than those in the model group. Moreover, it has also been reported that Astragalus [18] and Poria [19] can protect lipopolysaccharide-induced intestinal mucosal injury by reducing the production of inflammatory cytokines, such as IL-1β, and TNF-α through inhibiting the NF-κB signaling pathway. Atractylodes [20] and Pinellia ternata [21] can promote cell proliferation and repair by inhibiting the proapoptotic gene (Bax) expression through polyaminemediated Ca 2+ signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…NFKBIA, known as I-kappa-B-alpha (I-κBα), which inhibits the activity of dimeric NF-kappa-B/REL complexes, has been reported as a target for glucocorticoid-mediated immunosuppression [44]. It has been demonstrated that the extract of PC can reduce the production of inflammatory mediators by suppressing the NF-κB signaling pathway [45]. Although all TLRs could lead to NF-κB activation, we found that ZDW might be more sensitive to an LPS-induced TLR4/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%